Thermal Stability and Radiation Tolerance of Lanthanide-Doped Cerium Oxide Nanocubes - Kory Burns; Paris C. Reuel; Fernando Guerrero; Eric Lang; Ping Lu; Assel Aitkaliyeva; Khalid Hattar; Timothy J. Boyle (Crystals, 2021)
The thermal and radiation stability of free-standing ceramic nanoparticles that are under consideration as potential fillers for the improved thermal and radiation stability of polymeric matrices were investigated by a set of transmission electron microscopy (TEM) studies. A series of lanthanide-doped ceria (Ln:CeOx; Ln = Nd, Er, Eu, Lu) nanocubes/nanoparticles was characterized as synthesized prior to inclusion into the polymers. The Ln:CeOx were synthesized from different solution precipitation (oleylamine (ON), hexamethylenetetramine (HMTA) and solvothermal (t-butylamine (TBA)) routes. The dopants were selected to explore the impact that the cation has on the final properties of the resultant nanoparticles. The baseline CeOx and the subsequent Ln:CeOx particles were isolated as: (i) ON-Ce (not applicable), Nd (34.2 nm), Er (27.8 nm), Eu (42.4 nm), and Lu (287.4 nm); (ii) HMTA-Ce (5.8 nm), Nd (6.6 nm), Er (370.0 nm), Eu (340.6 nm), and Lu (287.4 nm); and (iii) TBA-Ce (4.1 nm), Nd (5.0 nm), Er (3.8 nm), Eu (7.3 nm), and Lu (3.8 nm). The resulting Ln:CeOx nanomaterials were characterized using a variety of analytical tools, including: X-ray fluorescence (XRF), powder X-ray diffraction (pXRD), TEM with selected area electron diffraction (SAED), and energy dispersive X-ray spectroscopy (EDS) for nanoscale elemental mapping. From these samples, the Eu:CeOx (ON, HMTA, and TBA) series were selected for stability studies due to the uniformity of the nanocubes. Through the focus on the nanoparticle properties, the thermal and radiation stability of these nanocubes were determined through in situ TEM heating and ex situ TEM irradiation. These results were coupled with data analysis to calculate the changes in size and aerial density. The particles were generally found to exhibit strong thermal stability but underwent amorphization as a result of heavy ion irradiation at high fluences.